2021
DOI: 10.1021/acs.jpcc.1c02091
|View full text |Cite
|
Sign up to set email alerts
|

Giant Linear and Nonlinear Excitonic Responses in an Atomically Thin Indirect Semiconductor Nitrogen Phosphide

Abstract: Large linear and nonlinear optical responses can be obtained from two-dimensional semiconductors with an indirect electronic gap. Here, we demonstrate exceptionally large exciton-driven responses such as the fundamental exciton binding energy (2 eV), zeropoint band-gap renormalization (200 meV), and nonlinear second and third harmonic coefficients (800 pm/V and 1.4 × 10 −18 m 2 /V 2 , respectively) from an atomically thin binary group-V nitrogen phosphide (NP) semiconductor. The influence of lattice vibrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 129 publications
1
13
0
Order By: Relevance
“…Recently, Kolos et al found that mixed V group electron-based materials can exhibit strong exciton effects and the properties can be temperature-dependent. 36 So, we focus on the effect of temperature on the thermal properties of the devices made up of these phases. Finally, we estimate thermoelectric properties of the phases considered by designing them as simple one-dimensional devices and calculating their Seebeck coefficients and thermoelectric preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kolos et al found that mixed V group electron-based materials can exhibit strong exciton effects and the properties can be temperature-dependent. 36 So, we focus on the effect of temperature on the thermal properties of the devices made up of these phases. Finally, we estimate thermoelectric properties of the phases considered by designing them as simple one-dimensional devices and calculating their Seebeck coefficients and thermoelectric preferences.…”
Section: Introductionmentioning
confidence: 99%
“…A similar situation is also observed during the stabilization of monolayer β-NP, which falls under the same family. 27 Also, buckled hexagonal structures of silicene and germanene, which show negative phonon frequencies, 45 were experimentally prepared on substrate of Ag 46 and Al. 47 We finally note that several buckled V−V binary materials were experimentally prepared recently.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…32 Nevertheless, shifting the focus from the traditional planar monolayers, Taheri et al 33 demonstrated that group V monolayers based on nitrogen (NX, where X = P, As, and Sb) in their β-phase exhibit thermodynamically stable buckled structures. Using a purely ab initio technique (along with a temperature dependent BSE calculation), it was recently shown 27 that this β-phase nitrogen phosphide (NP) monolayer can exhibit a very high excitonic binding energy and strong absorbance spectra in the visible region. The nonlinear coefficients SHG along with the third harmonic generation (THG) were also found to be very high compared to the traditional TMDs and monolayer transitional metal monochalcogenides (TMMCs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…[40,41] The vacuum layer exceeding 20 Å was set along the z-axis to avoid spurious interaction between neighbor layers. [42] In the structural optimization, the lattice vectors and atomic positions were constrained in the x and y direction, and the maximum allowable value was 0.01 eV Å À1 . For heterostructures, the semiempirical DFT-D3-corrected long-range vdW interaction was considered.…”
Section: Computational Detailsmentioning
confidence: 99%